Hubungan Smartphone Addiction Terhadap Text Neck Syndrome Pada Mahasiswa Program Studi Sarjana Kedokteran dan Profesi Dokter Fakultas Kedokteran Universitas Udayana Angkatan 2019 dan 2020 - Laksmi, A. A. Ayu Widya; Wardana, I Nyoman Gede; Widianti, I Gusti Ayu; Muliani, Muliani (Universitas Udayana, 2022)
Text neck syndrome in the 21st century has the risk of becoming a condition that needs more attention. The development of technology, such as computers, laptops, and smartphones, causes the text neck syndrome to arise. The use of smartphones is one of the important factors causing text neck syndrome. Intense smartphone use accompanied by poor posture when using a smartphone can indicate repetitive neck pain and stiffness. Based on those background, aim of this study is to determine the prevalence of text neck syndrome, smartphone addiction and relationship between smartphone addiction and text neck syndrome in students medicine graduate program of the Faculty of Medicine, Udayana University batch 2019 and 2020. This study was a descriptive analytic cross-sectional study. Sampling using purposive sampling technique. There are 489 respondents who are students of the 2019 and 2020 Bachelor of Medicine and Doctoral Profession Study Program. Data collection is done online through google from which is accompanied by NDI and SAS-SV questionnaires. Data analyzed, by Chi Square test and was processed using SPSS version 26. The results show prevalence of text neck syndrome are 183 (37.4%) and prevalence for smartphone addiction are 339 (69.3%). Chi square tests showed that there was a relationship between smartphone addiction and text neck syndrome (p=0.000) PR=3.670 (CI 95%; 2.310-5.832). Keywords : smartphone addiction, text neck syndrome, neck disability